Imaginary companions, theory of mind and emotion understanding in young children. Issue 2 (3rd March 2016) - Giménez-Dasí, Marta; Pons, Francisco; Bender, Patrick K.
ABSTRACT: The phenomenon of imaginary companions (ICs) has received little attention in developmental psychology, even though it can be observed in approximately 25% of preschool-aged children. Only a few studies have investigated the effect of ICs on children's theory of mind and emotion understanding, and the results are partial or inconsistent. This study used comprehensive measures to assess emotional understanding and theory of mind in children aged four to six with ICs ( N = 24) and compared their performance to that of children without ICs ( N = 24). Results showed that children with ICs, regardless of age and gender, have a better theory of mind and emotion understanding than children without ICs. The greatest impact of ICs was on girls' emotion understanding. The results are discussed in relation to gender differences.